Emotions, Morality, and Cognition: The Unprecedented Scope of the Concept of the Heart in Amharic - Kacprzak, Aleksander (Aethiopica, 2024)
This study sheds light on the unique conceptualization of the heart in Amharic, based on dictionary data, corpus data, and a self-collected corpus of text excerpts. What stands out is the unusually vast scope of the concept, which embraces not only emotions, character and morality, but also cognition, and, to some extent, rationality. Thus, the noun ləbb can, depending on the context, be translated into English as ‘mind’, ‘good sense’, or even ‘reason’. The broad scope of the concept is even better seen in light of the derivatives of the word ləbb, most notably the noun ləbbuna / ləbbona, connected with psyche, reason, and the sense of right and wrong, as well as the adjectives ləbbam and ləbbeñña, meaning ‘intelligent, attentive’. The uniqueness of the Amharic worldview is also reflected in the conceptualizations underlying the single idiomatic phrases formed with the noun ləbb, as well as the connection it has to the other parts of the Amharic worldview. Particularly worth highlighting here is the figure of God, around whom the whole Amharic worldview revolves, as well as the concept of aʾǝməro ‘mind’, which does not introduce the same stark opposition between the mind and the heart as the one known from European languages and discourses.